Analisis Kepraktisan Modul Usaha dan Energi Berbasis Problem Based Learning - Lovisia, Endang; Febrianti, Yuli (Science and Physics Education Journal (SPEJ, 2024)
Abstract: This study aims to determine: Practicality of Problem Based Learning based energy and business module in terms of practicality. The method used in this research is a research and development approach which is usually known as the R&D research method. In this study using the 4D model design. The results showed that: 1) the average validity assessment of the three experts was 0.86 (very valid); 2) The limited group trial obtained 89% (very practical), the large group trial obtained 93% (very practical). Thus the learning module developed is valid, practical and feasible to use. Keywords: Module, Practicality, Problem-based learning.